Inscrições corporais: tatuagens, piercings e escarificações à luz da psicanálise - MOREIRA, Jacqueline de Oliveira (Universidade Federal do Pará, 2018)
This article is an attempt to apprehend contemporary discourses about the body and see this body as a space for subjective inscription. The article is the result of the interlocution among research projects that focus on the study of different types of body inscription and that are coordinated by the authors at three graduate programs. Taking psychoanalysis as the basis for our discussions, we study tattoos and scraping which, however distinct, are both seen as forms of language.